Apprenticeship, work, society in early modern venice
1 online resource (xvi, 288 pages)
Keywords: "Apprenticeship in early modern Europe has been the subject of important research in the last decades, mostly by economic historians, but the majority of the research has dealt with cities or countries in Northern Europe. The organization, evolution and purpose of apprenticeship in Southern Europe are much less studied, especially for the early modern period. The research in this volume is based on a unique documentary source: more than 54,000 apprenticeship contracts registered from 1575 to 1772 by the 'Old Justice', a civil court of the Republic of Venice in charge of guilds and labour disputes. An archival source of such scale provides a unique opportunity to historians and this is the first time that primary research on apprenticeship is leveraging such a large amount of data in one of the main economic centres of early modern Europe. This book brings together multiple perspectives including social history, economic history and art history and is the outcome of an interdisciplinary collaboration between historians and computer scientists. Apprenticeship, Work, Society in Early Modern Venice will appeal to students and researchers alike interested in the nature of work and employment in Venice and Italy as well as society in Early Modern Europe more generally"--